Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan pada CV. Karya Abadi Pratama Bukittinggi - Siska, Adilla Juita; Fadillah, M. Teguh (Jurusan PIPS FKIP UMMY Solok, 2022)
This study aims to determine how the effect of compensation and work discipline on employee performance CV. Karya Abadi Pratama Bukittinggi. Here the author describes the effect of compensation and work discipline on performance. The type of research conducted in this study uses quantitative and descriptive methods. The population in this study were all employees of CV. Karya Abadi Pratama Bukittinggi with a population sample of 51 employees. While the analytical method used in this study is multiple linear regression correlation analysis, and the coefficient of determination at a significant level of 5%. The results showed that the variables of compensation and work discipline had an effect on employee performance partially or simultaneously. Keywords: Compensation, Work Discipline, Performance